2018
DOI: 10.3389/fimmu.2018.00727
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Response to Autologous Dendritic Cell Therapy in Glioblastoma Multiforme

Abstract: BackgroundGlioblastoma (GBM) is the most common and lethal primary malignant glioma in adults. Dendritic cell (DC) vaccines have demonstrated promising results in GBM clinical trials. However, some patients do not respond well to DC therapy, with survival rates similar to those of conventional therapy. We retrospectively analyzed clinical and laboratory data to evaluate the factors affecting vaccine treatment.MethodsForty-seven patients with de novo GBM were enrolled at China Medical University Hospital betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 73 publications
(67 reference statements)
2
52
0
Order By: Relevance
“…Moreover, PD-L1 inhibits chemokine production (e.g., CCL2-5 and CXCL9-10) that is crucial for recruitment of CTL, preventing the influx of CTL into tumor microenvironment (Gajewski et al, 2013). The roles of PD-1/PD-L1 pathway in inducing CTL exhaustion and Treg augment in tumor microenvironment have been verified in various cancer models (Dong et al, 2017; Jan et al, 2018).…”
Section: Pd-l1 Modulating Immune Cell Infiltration In Glioma Microenvmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, PD-L1 inhibits chemokine production (e.g., CCL2-5 and CXCL9-10) that is crucial for recruitment of CTL, preventing the influx of CTL into tumor microenvironment (Gajewski et al, 2013). The roles of PD-1/PD-L1 pathway in inducing CTL exhaustion and Treg augment in tumor microenvironment have been verified in various cancer models (Dong et al, 2017; Jan et al, 2018).…”
Section: Pd-l1 Modulating Immune Cell Infiltration In Glioma Microenvmentioning
confidence: 94%
“…The increase of PD-L1 + TIM surrounding glioma cells is associated with strong immune inhibition (Liu et al, 2008; Mirghorbani et al, 2013; Hosseini et al, 2015). Jan et al (2018) found that lower PD-L1 level in glioma cells is associated with neither abating immune inhibition nor better prognosis of glioma, which is probably linked with elevated PD-L1 + TIM in glioma microenvironment.…”
Section: The Prognostic Value Of Pd-l1 In Glioma Patientsmentioning
confidence: 99%
“…It is widely accepted that PD-1 is an exhaustion marker for CTL (134), which is the main anti-tumor effector cell during checkpoint blockade therapy. A study aiming to find predictors of DC vaccine responses showed that glioblastoma patients with tumor-infiltrating lymphocytes (TILs) with a higher PD-1 + /CD8 + ratio had worse prognosis (135). These data indicated that DC vaccine-primed CD8 + T cells became exhausted via the PD-1-PD-L1 axis, which is one of the reasons that DC vaccines have showed unsatisfactory results in osteosarcoma patients.…”
Section: Combination Therapy With Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…Hsu and colleague revealed a statistically significant correlation between higher degrees of TCR repertoires and prolonged overall survival in autologous tumor lysate-pulsed DC vaccines-treated GBM patients [ 87 ]. In a prospective case control study that enrolled 47 GBM patients with DC vaccine adjuvant therapy, better outcomes were predicted with younger age and a lower programmed cell death protein 1 (PD-1) + /CD8 + ratio in TILs and PBMCs [ 90 ]. Further analysis of the immune system factors demonstrated that the patients with an immune system equipped with favorable pre-existing or post-vaccination anti-tumor capabilities, such as IFN γ secretion and CD8 + cells, are more likely to live longer [ 91 ].…”
Section: Introductionmentioning
confidence: 99%